A mechanism for basal vacancy loop formation in zirconium. (November 2019) - Dai, C.; Saidi, P.; Topping, M.; Béland, L.K.; Yao, Z.; Daymond, M.R.
Abstract: Experiments and molecular dynamics were combined to determine a formation mechanism for basal vacancy loops in zirconium. In scanning/transmission electron microscopy images with different tilting angles, the majority of prismatic loops lying on a given basal plane do not align on a trace, but are seemingly randomly distributed in the plane. Similar arrangements are observed in molecular dynamics simulations. Over 200 collision cascade simulations were performed. Basal cascade-induced dislocation segments are observed in arrangements with a high density of prismatic vacancy loops, consistent with earlier experimental observations. This mechanism of basal c-loop formation may explain the experimentally observed incubation period. Graphical abstract: Unlabelled Image